Arachidonic acid has protective effects on oxygen-glucose deprived astrocytes mediated through enhancement of potassium channel TREK-1 activity. (1st January 2017) - Lu, Li; Zhang, Guangru; Song, Chunli; Wang, Xuexi; Qian, Weina; Wang, Zhuanling; Liu, Yanan; Gong, Sheng; Zhou, Shuning
Highlights: AA suppressed glutamate uptake and decreased GLT-1 levels under normal conditions. AA alleviated OGD-induced astrocyte death. AA rescued the decreased glutamate uptake under OGD conditions. AA increased expression levels of GLT-1 and TREK-1 under OGD conditions. Abstract: Polyunsaturated fatty acids (PUFAs) have neuroprotective effects against ischemic brain diseases. The newly discovered potassium channel "TREK-1" is a promising target for therapies against neurodegeneration. Arachidonic acid (AA) is an n-6 PUFA, as well as a potent TREK-1 activator. We previously showed that TREK-1 is expressed at high levels in astrocytes. However, the effect of AA on astrocytes in ischemia remains unknown. Here, we assessed the effects of 3–30 μM AA on astrocyte apoptosis, glutamate uptake, and expression of the astrocytic glutamate transporter 1 (GLT-1) and TREK-1 under different conditions. Under normal conditions, 3–30 μM AA showed no effect on astrocytic apoptosis or TREK-1 expression, whereas glutamate uptake decreased significantly and its change paralleled the decreased expression of GLT-1. When astrocytes were subjected to 4 h of oxygen-glucose deprivation (OGD), 10 μM AA markedly alleviated OGD-induced cell death, recovering from 63.50 ± 1.90% to 82.96 ± 4.63% of the control value. AA also rescued the decreased glutamate uptake and increased mRNA, as well as protein levels of GLT-1 and TREK-1. Our results provide new evidence of a protective effect of AA on astrocytes under OGD conditions, suggesting that a low concentration of AA may protect against brain ischemic diseases.